X-12=43

Simple and best practice solution for X-12=43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-12=43 equation:


Simplifying
X + -12 = 43

Reorder the terms:
-12 + X = 43

Solving
-12 + X = 43

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + X = 43 + 12

Combine like terms: -12 + 12 = 0
0 + X = 43 + 12
X = 43 + 12

Combine like terms: 43 + 12 = 55
X = 55

Simplifying
X = 55

See similar equations:

| 5-5(6-5)= | | 6(1-4p)=-8(-4+4p)-2 | | 61-3x=13-9x | | -6x-3.2=-3x+4.4 | | -9(6+n)=-54 | | -4.3+(-9.3)= | | 3x^2y+5y=2x | | v=(3.14)(36)(16) | | 3(2x-1)-6(x-4)=-9 | | -8(1-2k)=8(k-3) | | 46+2=3(5x+1) | | (x^4)-(10x^3)+(21x^2)+40x-100=0 | | 5+16z-3=9z+93-6z | | 49-2x=9-7x | | 5a=2a+7 | | x=1.4-(1.2x) | | X+6.5=9.7 | | 5+3x=-2x | | -3+6v=3(3v+4) | | 4(5x+3)-5(2x+1)=27 | | 4x+9=40-3x | | 3(3x+1)=39 | | 6a=6a+7 | | -38-8x=-3(-6+5x) | | 4+12x=4+x | | 2x^2y+xy-100=0 | | 4+x=3x-2 | | 3.2+6=6m-15 | | 5m=8m-15 | | -(r-5-8p)= | | 4M+3M=12 | | 8(5+13x)-(-2x+8)=32 |

Equations solver categories